Assessment of Genotoxicity of Zinc Oxide Nanoparticles Using Mosquito as Test Model - Kanwaljit Kaur Ahluwalia; Kritika Thakur; Amrik Singh Ahluwalia; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd_Allah; Neelam Thakur (Toxics, 2023)
The widespread applications of ZnO NPs in the different areas of science, technology, medicine, agriculture, and commercial products have led to increased chances of their release into the environment. This created a growing public concern about the toxicological and environmental effects of the nanoparticles. The impact of these NPs on the genetic materials of living organisms is documented in some cultured cells and plants, but there are only a few studies regarding this aspect in animals. In view of this, the present work regarding the assessment of the genotoxicity of zinc oxide nanoparticles using the mosquito Culex quinquefaciatus has been taken up. Statistically significant chromosomal aberrations over the control are recorded after the exposure of the fourth instar larvae to a dose of less than LD20 for 24 h. In order to select this dose, LD20 of ZnO NPs for the mosquito is determined by Probit analysis. Lacto-aceto-orcein stained chromosomal preparations are made from gonads of adult treated and control mosquitoes. Both structural aberrations, such as chromosomal breaks, fragments, translocations, and terminal fusions, resulting in the formation of rings and clumped chromosomes, and numerical ones, including hypo- and hyper-aneuploidy at metaphases, bridges, and laggards at the anaphase stage are observed. The percentage frequency of abnormalities in the shape of sperm heads is also found to be statistically significant over the controls. Besides this, zinc oxide nanoparticles are also found to affect the reproductive potential and embryo development as egg rafts obtained from the genetic crosses of ZnO nanoparticle-treated virgin females and normal males are small in size with a far smaller number of eggs per raft. The percentage frequencies of dominant lethal mutations indicated by the frequency of unhatched eggs are also statistically significant (p < 0.05) over the control. The induction of abnormalities in all of the three short-term assays studied during the present piece of work indicates the genotoxic potential of ZnO NPs, which cannot be labeled absolutely safe, and this study pinpoints the need to develop strategies for the protection of the environment and living organisms thriving in it.